Insurers monitor shocks to collateral: Micro evidence from mortgage-backed securities - Thiemo Fetzer; Benjamin Guin; Felipe Netto; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
This paper uncovers if and how insurance companies react to shocks to collateral in their portfolio of securitized assets. We address this question in the context of commercial real estate cash flow shocks, which are informationally opaque to holders of commercial mortgage-backed securities (CMBS). Using detailed micro data, we show that cash flow shocks during the COVID-19 pandemic predict CRE mortgage delinquency, especially those stemming from lease expiration of offices, reflecting lower demand for these properties. Insurers react to such cash flow shocks by selling more exposed CMBS-mirrored by a surge in small banks holding CMBS-and the composition of their CMBS portfolio affects their trading behavior in other assets. Our results indicate that institutional investors actively monitor underlying asset risk, and even gain an informational advantage over some banks.
Keywords: G20; G21; G22; G23; 330; Insurance Sector; Risk Management; Mortgage Default; Commercial Real Estate; CMBS; Work-from-home